"Pardon Those Who Have Wronged You for the First Time": Ambrose's Conception of venia and Its Use in His Letters to Theodosius I (Ep. 61–62). Issue 1 (2nd January 2019) - Türel, Tunç
ABSTRACT: This article deals with two specific letters written by Ambrose after the civil war between the usurper Eugenius and the emperor Theodosius I in 394. In both letters, which are directed to Theodosius I to urge him to grant pardon to the defeated party of Eugenius, we read Ambrose praising venia (mercy) as a virtue that needs to be practised in imitation of the Christian God. When taken at face value, the letters and the bishop appear to have played a major role in influencing Theodosius I's decision of pardon which followed shortly after the battle. When the history of granting pardon is examined, however, it becomes apparent that Ambrose's venia is in fact not very different from the mercy which had been practised by the Roman emperors, Theodosius I included, towards their enemies since the days of Julius Caesar. With the assertion of this practice, the self-declared intercessor Ambrose's letters, which were written in the vein of other letters of antiquity that almost always pursued the goal of showing off one's literary skills and therefore should be read with caution, should be considered no more than two letters gilded with Christian rhetoric to convey the bishop's version of events to posterity.